Whiteboard Animation in Fiqh Learning on Students of MI Mutiara Bunda’s Students - Murihah, Zaimatul (Interdisciplinary Social Studies, 2022)
To support the success of education in schools, technology, methods, strategies, media are needed in learning in the classroom so that students can quickly understand and be motivated in learning but the reality in the field is different. This study aims to apply whiteboard animation learning media to measure students' critical thinking in Fiqih lessons. The research method used is quantitative field experiments. The subjects of this study were students at MI Mutiara Bunda Surabaya, 20 samples were taken consisting of 10 students in the control class and 10 students in the experimental class. The four stages of trials that have been carried out, include: First, a questionnaire test with tcount > ttable (11,831 > 2,262) for the control class and (33,541 > 2,262). Significance 0.000, since the significance of < 0.05 then Ho was rejected and Ha was accepted. Second, an oral test with tcount greater than ttable (6,497 > 2,262), then Ho was rejected and Ha was accepted. The three questionnaire tests with a score of tcount > ttable (148,500 > 2,262) then Ho was rejected and Ha was accepted. The four reliability and validity tests with Cronbach's alpha score of 0.768 > 0.60, then as the basis for decision making in the reliability test above. The conclusion is that the learning medium of whiteboard animation is very well used against students' critical thinking in Fiqh subjects.